Competitive pressure and firm investment efficiency: Evidence from corporate employment decisions. (4th October 2021) - Boubaker, Sabri; Dang, Viet A.; Sassi, Syrine
Abstract: This study examines the link between product market competition and labour investment efficiency. We find that competitive pressure distorts the efficiency of corporate employment decisions by creating an underinvestment problem. This finding withstands a battery of robustness checks and remains unchanged after accounting for endogeneity concerns. Additional analysis shows that the relationship between product market competition and labour investment efficiency is stronger for firms facing higher competitive threats, greater financial constraints, higher information asymmetry and higher labour adjustment costs. Our results suggest that as competition increases bankruptcy risk, it leads managers to underinvest in labour to avoid incurring labour‐related costs.